2014
DOI: 10.1093/cid/ciu784
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-like Disease in Infants Due to Human Parechovirus Type 3 During an Outbreak in Australia

Abstract: We report the largest series of HPeV-3 infection in infants, and the first outbreak in Australia. Infants presented with a severe sepsis-like syndrome with a high rate of ICU admissions, but all recovered from the acute infection without complications. Long-term sequelae are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(143 citation statements)
references
References 30 publications
12
120
2
1
Order By: Relevance
“…However, we think it is likely that all these cases are HPeV3 associated because they have a similar phenotype, they all occurred within a 6-month period, they are all from the east coast of Australia, and HPeV3 was identified among other specimens in state reference laboratories during the period. 34,39 Our study confirms features described in a similarly sized, retrospective series reported by Verboon-Maciolek et al, 3,40 and shows that young age and premature birth are possible risk factors for encephalitis in HPeV infection, that female gender is overrepresented, and that cranial ultrasound is an inadequately sensitive imaging modality in this disease. We also show that, although short-term outcomes may be reassuring, a high proportion of infants experience neurodevelopmental sequelae.…”
Section: ; Nil/minor Sequelae Signifi Cant Concernsupporting
confidence: 89%
See 2 more Smart Citations
“…However, we think it is likely that all these cases are HPeV3 associated because they have a similar phenotype, they all occurred within a 6-month period, they are all from the east coast of Australia, and HPeV3 was identified among other specimens in state reference laboratories during the period. 34,39 Our study confirms features described in a similarly sized, retrospective series reported by Verboon-Maciolek et al, 3,40 and shows that young age and premature birth are possible risk factors for encephalitis in HPeV infection, that female gender is overrepresented, and that cranial ultrasound is an inadequately sensitive imaging modality in this disease. We also show that, although short-term outcomes may be reassuring, a high proportion of infants experience neurodevelopmental sequelae.…”
Section: ; Nil/minor Sequelae Signifi Cant Concernsupporting
confidence: 89%
“…34 In this report, most (75/118) cases had CNS infection confirmed by the presence of HPeV RNA on polymerase chain reaction (PCR); however, infants with mild CNS HPeV infection were not differentiated from those with more serious disease, due to the lack of application of formal clinical definitions of encephalitis. When compared with this retrospective series, our prospectively collected HPeV encephalitis cases were younger (median 13 days compared with median 39 days 34 ) and more likely to be girls (7/9 compared with 53/118 [45%] 34 ). This, and the high proportion of prematurity in our series suggests that young age may be a risk factor for encephalitis from HPeV infection, and that there may be a gender difference in susceptibility.…”
Section: ; Nil/minor Sequelae Signifi Cant Concernmentioning
confidence: 87%
See 1 more Smart Citation
“…The fraction of symptomatic HPeV-3-infected infants that develop sepsis-like illness can exceed 80 %; most such patients require hospitalization and up to one-third of them are admitted to the ICU [104][105][106]. The CNS symptoms of HPeV-3 infection can include meningitis, meningoencephalitis, encephalitis or cerebral haemorrhage, with occasional white-matter alterations [107,108]. Whereas HPeV-3 meningitis typically has a good prognosis, meningoencephalitis entailing white-matter alterations may have long-term sequelae, such as cerebral palsy, learning disabilities, epilepsy or visual impairment [34].…”
Section: Human Parechovirusmentioning
confidence: 99%
“…HPeV is a small RNA virus belonging to the Picornaviridae family of enteroviruses [1]. The genus contains six members, with HPeV 3 associated with neonatal infections presenting with symptoms in the central nervous system (CNS) [2].…”
Section: Introductionmentioning
confidence: 99%